Comparative Study of Pure Iron Manufactured by Selective Laser Melting, Laser Metal Deposition, and Casting Processes. Issue 7 (5th April 2019) - Carluccio, Danilo; Bermingham, Michael; Kent, Damon; Demir, Ali Gökhan; Previtali, Barbara; Dargusch, Matthew S.
Abstract : Laser‐based additive manufacturing (AM) processes such as laser metal deposition (LMD) and selective laser melting (SLM) can produce patient‐specific implants with minimal post‐processing and shorter lead times compared to conventional manufacturing methods. In this study, the microstructural, mechanical, and corrosion properties of cast, LMD, and SLM manufactured pure Fe for biodegradable biomedical implants were compared. It was found that casting resulted in an average grain size double that of pure Fe manufactured via LMD and over 30 times that when compared to parts manufactured using SLM. This was attributed to the higher cooling rates of the laser‐based AM technologies and led to superior mechanical properties of the samples manufactured via SLM. The corrosion rate of the LMD and SLM samples were approximately 50% higher than the cast pure Fe. For biodegradable Fe implants, a higher corrosion rate and yield stress are preferential, and combined with the ability to produce complex geometries, makes SLM a promising manufacturing technology for biodegradable implants such as bone scaffolds. Abstract : In this study the properties of cast, laser metal deposition (LMD) and selective laser melting (SLM) manufactured pure Fe were investigated. The cast Fe had an average grain size over 30 times that of SLM and double that of LMD. The corrosion rates of Fe manufactured via LMD and SLM were approximately fifty percent higher than its cast equivalent.